‎Fuzzy Cone Metric Spaces and Fixed Point Theorems for Fuzzy Type Contraction - Muhammed Raji; Laxmi Rathour; Lakshmi Narayan Mishra; Vishnu Narayan Mishra (Transactions on Fuzzy Sets and Systems)
The paper aims to introduce novel concepts of fuzzy type contractions and establish fixed point theorems for fuzzy mappings within the framework of fuzzy cone metric spaces‎. ‎These contributions extend the existing literature on fuzzy mappings and fixed point theory‎. ‎Through illustrative examples‎, ‎we showcase the practical applicability of our proposed notions and results‎, ‎demonstrating their effectiveness in real-world scenarios‎.